Penerapan SAK EMKM para pelaku usaha mikro kecil dan menengah (UMKM) menuju pengembangan revolusi industri 4.0 (studi pada UMKM di Kabupaten Sidoarjo) - Datuk Maralelo Siregar (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
Micro, Small, and Medium Enterprises (MSMEs) play an essential role in the Indonesian economy. This study aims to determine whether Micro has implemented the application of SAK EMKM financial statements, Small and Medium Enterprises (UMKM) entrepreneurs in Sidoarjo Regency and aims to determine whether business development has begun to follow the Industrial Revolution Era 4.0. The data analysis technique used in this study is descriptive-qualitative analysis with data collection by describing, telling, and interpreting the meaning of the data that has been collected. Based on the study results, MSME actors have not implemented the recording of financial statements by SAK EMKM because they have obstacles in understanding financial statements by the existing SAK EMKM. Therefore many MSME actors do simple recordings. Meanwhile, for business development, MSME actors have started to develop their business by utilizing existing sales applications provided and producing with the help of machines even though there are still those who traditionally sell and make. However, there are still MSME actors who have not taken advantage of the online applications provided